CROSS-BORDER MEDICAL TOURISM: A TYPOLOGY AND AGENDA FOR RESEARCH FOR THE SOUTH-EAST ASIAN REGION - PHUA, KAI-LIT (ITB Journal Publisher, LPPM ITB, 2008)
Cross-border medical tourism can be broadly divided into two types, i.e. price-sensitive and quality sensitive. Price-sensitivity increases the likelihood of “lower cost overseas treatment” and qualitysensitivity promotes “higher cost overseas treatment”. As medical tourism grows in Southeast Asia, home and host countries (a country may be both simultaneously) will be differentially affected. Medical tourism, in actuality an increase in demand for certain kinds of medical services (albeit by foreigners), may accelerate movements of health personnel, i.e., from poorer to richer countries, from the public sector to the private sector within host countries, and from less lucrative to more lucrative sub-sectors within the private sector. Foreign medical care investment may also be enhanced in certain countries. An agenda for research on specific issues such as patient characteristics and treatments likely to be sought is proposed in this article.